Implementation of the Kitabah Method in Qur’an Reading Instruction for Deaf Students at SLB Muhammadiyah Purworejo - Ahmad Salman Zayn; M.Nurul Huda (Edusoshum : Journal of Islamic Education and Social Humanities, 2026)
To successfully teach deaf students to read the Qur’an, an instructional approach is required that considers limitations in the processing of auditory information. This study aims to analyze the implementation of kitabah (writing-based) method in Qur’an reading instruction for second-year junior high school deaf students at SLB Muhammadiyah Purworejo and to analyze its contribution to the development of their reading skills. The approach used is descriptive qualitative. The subjects of this study were Islamic Religious Education teachers and deaf students. The data were collected thru observation, in-depth interview, and documentation. The data were analyzed thru data reduction, data presentation, and conclusion drawing. The data obtained were analyzed and validated by using source and technique triangulation. The results indicate that kitabah method which consists of seeing, writing, and re-reading can improve the recognition process of hijaiyah (Arabic) letters. After the application of the method, the student’s ability to recognize the Hijaiyah letters increased from 60% to 90%, and the ability to distinguish between letters with similar shapes increased from 40% to 85%. As well as these gains, students made progress in reading simple words, neatness of handwriting, participation and confidence to read independently. Results suggest that the main contribution of the kitabah approach is an emphasis on the use of writing activities to connect the visual form of the letters with reading skills and not to view writing as a mechanical exercise. Thus, the kitabah method is an adaptive and inclusive method for teaching the Qur'an to deaf students as it allows the learning process to be adapted to their specific visual and motor characteristics.